Increased Regulatory T Cells and Decreased Myeloid-Derived Suppressor Cells Induced by High CCL17 Levels May Account for Normal Incidence of Cancers among Patients with Atopic Dermatitis - Morimura, Sohshi (Int J Mol Sci, 2021)
The incidence of cancers in atopic dermatitis (AD) is not increased, although the Th2-dominant environment is known to downregulate tumor immunity. To gain mechanistic insights regarding tumor immunity in AD, we utilized CCL17 transgenic (TG) mice overexpressing CCL17, which is a key chemokine in AD. Tumor formation and lung metastasis were accelerated in CCL17 TG mice when melanoma cells were injected subcutaneously or intravenously. Flow cytometric analysis showed increases in regulatory T cells (Tregs) in lymph nodes in CCL17 TG mice with high mRNA levels of IL-10 and Foxp3 in tumors, suggesting that Tregs attenuated tumor immunity. The frequency of myeloid-derived suppressor cells (MDSCs), however, was significantly decreased in tumors of CCL17 TG mice, suggesting that decreased MDSCs might promote tumor immunity. Expression of CXCL17, a chemoattractant of MDSCs, was decreased in tumors of CCL17 TG mice. Depletion of Tregs by the anti-CD25 antibody markedly reduced tumor volumes in CCL17 TG mice, suggesting that tumor immunity was accelerated by the decrease in MDSCs in the absence of Tregs. Thus, CCL17 attenuates tumor immunity by increasing Tregs and Th2 cells, while it decreases MDSCs through reductions in CXCL17, which may work as a “safety-net” to reduce the risk of malignant tumors in the Th2-dominant environment.